Orientasi Tafsir Turjuman Al-Mustafid Karya Abdur Rauf Al-Singkili - Sahlan Muhammad Faqih; Dadan Rusmana; Yayan Rahtikawati (JURNAL AT-TURAS, 2022)
This article discusses the study of the interpretation orientation (ittijah al-mufassir) of Tarjuman al-Mustafid, as a pioneer in the development of the 'fardi' (individual) interpretation of Nusantara in the Century. This article uses a qualitative approach and an exploratory-phenomenological approach. Al-Singkili's scientific odyssey to the Arabian Peninsula to the 'maqam' that has matured in various sciences. After returning to Aceh, al-Singkili was appointed mufti of the kingdom by contributing to the thought and administrative aspects. The lineage of thought of the sanad al-Singkili is directly related to the author of 'Tafsir al-Jalalain'. As a stream of practical Sufism (Tasawwuf Al-'Amali) and the depth of Shari'a knowledge that he controls, he always thinks moderately in making decisions and religious fatwas. This can be done in his response when faced with a mystical dispute that occurred between the thoughts of Hamzah al-Fanzhuri and Nuruddin al-Raniri. Al-Singkili tried to be moderate without making accusations, but did not agree with al-Raniri's position. This wasathiyyah thought can be found in the explanations presented in his commentary when faced with anthropopomorphic verses.